Estudio De Un Modelo Asociativo Para Los Productores De Piña Del Departamento Del Huila, Con El Fin De Atender El Mercado Canadiense De Piña Deshidratada Tipo Snack - Aguirre Perafan, Nataly Nataly (Universidad Antonio Nariño, 2023)
The purpose of this research is to propose an associative model for pineapple producers in the department of Huila. Throughout this document, the interest of farmers in this area to belong to this model isidentified, taking into account the socio- of all the regions of Colombia deepening in the Region of the department of Meta, where the pineapple farmers are located, likewise the characteristics of this fruit are taken into account.